Trends in HIV Infections and AIDS Cases in Tokyo: Considerations for Prevention Strategies - Kashiwagi, Yoshiyuki (Global Indonesia Health Care (GOICARE), 2026)
Background: Human immunodeficiency virus (HIV) infection is a global public health challenge. In Japan, transmission among men who have sex with men (MSM) continues to dominate the pandemic. Purpose: This study examined trends in newly reported HIV infections and acquired immunodeficiency syndrome (AIDS) cases in Tokyo in fiscal year (FY) 2024, focusing on demographic characteristics, transmission routes, and testing patterns to inform future preventive strategies. Methods: We conducted a retrospective descriptive analysis of open-access surveillance data and official records from public health centers and municipal HIV counselling/testing services in the Tokyo Metropolitan area. The data included reported HIV infections, AIDS cases, and testing performance in 2024. Results: In FY2024, Tokyo reported 228 HIV and 62 AIDS cases (total: 290), the second-lowest annual total in the past decade. Sexual contact accounted for 80.0% of the transmissions, of which 69.3% were MSM. Approximately 70% of HIV cases occurred in individuals aged 20–39 years, while 80% of AIDS cases occurred in those aged 30–59 years. The HIV positivity rate has declined to 0.31%, the lowest in the past decade, coinciding with recovery in testing volumes post-COVID-19 and an upsurge in testing associated with a concurrent syphilis outbreak. Notably, HIV testing among men aged ≥60 years increased by 23% compared with pre-pandemic lows, although the positivity rates remained stable. Conclusion: Although HIV incidence in Tokyo has fallen over the decade, AIDS case counts have stayed stable or risen, highlighting the need for earlier diagnosis and treatment. Prevention should prioritize MSM, engage older adults seeking testing, expand targeted community-based outreach, and strengthen sex education addressing same-sex transmission risks. Relevance to clinical practice: Findings support nurse-led, competent prevention in Tokyo: prioritize MSM and older adults; expand community testing/counseling, promote self-initiated screening, accelerate linkage to ART, and improve PrEP access and inclusive sex education